PENGARUH DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI DINAS PERHUBUNGAN KOMUNIKASI INFORMATIKA KOTA SERANG - Kurnianingsih, Asih; Zulkarnain, Rizal (Universitas Banten Jaya, 2023)
ABSTRACT The one indicator of employee is if the employer has a good performance or not wheres the employee has a good discipline level of work, the influence of labor discipline can affect the quality of employee performance. Department of Transportation, Communications and Information Technology is one of the government of Serang city who gives service for citizen, so if an employee's performance is not good, then would gives affect for the service. This study the researcher tried to do in-depth study of whether there was an effect on the performance of labor discipline of employees in the Department of Transportation, Communication and Information of Serang City. The method used is descriptive and associative. This study uses literature and field research such as interviews, observation and questionnaires for 46 employerBased on Hypothesis Testing showed that the value of t count> t table (4.374> 1.6802), then Ho is rejected and Ha accepted. Means a significant difference between the performance of employees working diciplinje at the Department of Communication and Information Kota Serang.